2006
DOI: 10.1080/03079450600821141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heterophil granulocyte depletion caused by 5-fluorouracil on infectious bursal disease virus infection in specific pathogen free chickens

Abstract: The purpose of this study was to investigate the influence of the cytostatic drug, 5-fluorouracil (5-FU), which causes depletion of heterophil granulocytes, on clinical symptoms and histological lesions during the progress of infectious bursal disease virus (IBDV) infection in chickens. The aim was to disclose the mechanism behind the clinical disease symptoms. Three groups of specific pathogen free chickens were used for the experiment. Chickens in groups 1 and 3 were pretreated with 5-FU, while chickens in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Therefore, transmission electron microscopy does not confirm that the primary target of IBDV would be the ERC. The Mal is loaded with viruses, therefore based on our earlier findings, we have proposed that the BSDC is the primary target of IBDV ( Kabell et al, 2006 ), which was confirmed by Yasmin et al (2015) .…”
Section: Function Of Bsdcmentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, transmission electron microscopy does not confirm that the primary target of IBDV would be the ERC. The Mal is loaded with viruses, therefore based on our earlier findings, we have proposed that the BSDC is the primary target of IBDV ( Kabell et al, 2006 ), which was confirmed by Yasmin et al (2015) .…”
Section: Function Of Bsdcmentioning
confidence: 65%
“…The cytokine storm drives the chB6 positive, but virus-free B cell into the interfollicular space ( Shah et al, 2021 ) which suggests that the B cells are not the primary target of IBDV ( Shah et al, 2021 ). Our earlier studies provide evidence that at least 2 kinds of cells are essential for the clinical outbreak of IBDV infection: intrabursal BSDC and a bone marrow-derived heterophil granulocyte ( Kabell et al, 2006 ). After IBDV infection, the BSDC rapidly transform to Mal and migrate into the cortex, initiating heterophil invasion and subsequently cytokine storm.…”
Section: Function Of Bsdcmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of the heterophils entering the BF increase with acute IBDV infection (Lam, 1998). Kabell et al (2006) have studied the effect of IBDV after pretreating the three groups with 5-fluorouracil, a placebo and 5-fluorouracil, and the results indicated that heterophil granulocytes, together with the bursal secretory DCs, contribute to the outbreak and may progress clinical symptoms. IBDV in vitro alter the functioning of heterophils, with decreases in cell migration and phagocytic activity whilst it activates cellular oxidative bursts and increases cellular adherence to the IBDV-infected chicken embryo fibroblasts of the heterophils.…”
Section: Heterophilsmentioning
confidence: 99%
“…In the cells of the IFE, we were unable to identify virus particles with IBDV cytochemistry or transmission microscope; however, the presence of malformed granules shows that IBDV infection deeply interferes with the Golgi function, glycosylation. It is not apparent whether the Golgi complex has been influenced directly by the virus or by some biologically active factor(s) released from other infected cells, namely BSDC transformed to Mals [ 13 , 17 ] or heterophil granulocytes [ 20 ] which enter the IFE.…”
Section: Resultsmentioning
confidence: 99%